2001
DOI: 10.1074/jbc.m011338200
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Acutely Stimulates Na+/H+Exchanger (NHE3) Endocytosis via Clathrin-coated Vesicles

Abstract: Extracellular fluid volume and to a certain extent blood pressure in mammals are determined by the balance between sodium intake and renal sodium excretion (1, 2). As regulator of sodium excretion, the intrarenal autocrine-paracrine dopamine (DA) 1 system assumes far greater importance than circulating endocrine or neurogenic dopamine (3-6). DA is produced in the proximal tubule via decarboxylation of its precursor L-dihydroxyphenylalanine derived from the plasma and glomerular filtrate (7-9) and is then secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 98 publications
6
167
0
Order By: Relevance
“…It was recently shown that endocytosis of NHE3 occurs primarily via clathrin-coated pits (36,37) and that clathrin-mediated endocytosis requires an intact actin cytoskeleton (38). In support of trafficking, we demonstrated that the decrease of NHE3 activity induced by CPA is inhibited by cytochalasin B, which induces cytoskeletal disorganization (31) and reportedly has per se an inhibitory effect on NHE3 (31) (for effect of cytochalasin B, see also the Results section).…”
Section: Discussionmentioning
confidence: 72%
“…It was recently shown that endocytosis of NHE3 occurs primarily via clathrin-coated pits (36,37) and that clathrin-mediated endocytosis requires an intact actin cytoskeleton (38). In support of trafficking, we demonstrated that the decrease of NHE3 activity induced by CPA is inhibited by cytochalasin B, which induces cytoskeletal disorganization (31) and reportedly has per se an inhibitory effect on NHE3 (31) (for effect of cytochalasin B, see also the Results section).…”
Section: Discussionmentioning
confidence: 72%
“…Protein kinase A-mediated phosphorylation of NHE3 was also implicated in the internalization of NHE3 after the chronic exposure of cells to hormones that elevate cAMP (3), which suggested that, in the absence of NHERF-1, NHE3 localization may be modified. However, no difference was discernable in the apical localization of NHE3 in proximal tubules from WT and NHERF-1(Ϫ͞Ϫ) mice, which could ref lect a low rate of NHE3 recycling under basal or resting conditions (41) or functional compensation by NHERF-2 to maintain NHE3 at the apical membrane. Recent studies have also suggested a direct link between NHE3 and the actin cytoskeleton (41), which may also play a role in the membrane localization and activity of the antiporter.…”
Section: Discussionmentioning
confidence: 97%
“…It is uncertain whether this ion transport is due to an increase in the intrinsic activity of the transporters and/or an increase in their number at the membrane. Indeed, NHE3 undergoes continuous recycling between the plasma membrane and the large pool of subcellular endosomes (9,10), and redistribution between these pools was suggested to contribute to the regulation of exchange activity (11). Whether the transporter trafficking is downstream of the flow stimulation, however, remains unknown.…”
mentioning
confidence: 99%